Soil amendment and N fertilization strategies to improve C sequestration and storage in soil aggregates - Andrade, Maria Gabriela de Oliveira [UNESP]; Cordeiro, Carlos Felipe dos Santos [UNESP]; Calonego, Juliano Carlos [UNESP]; Franzluebbers, Alan; Rosolem, Ciro Antonio [UNESP] (Wiley, 2024)
Management can affect soil quality through changes in carbon (C) stock, especially in protected C fractions of soil aggregates. Soil aggregation and C sequestration may be improved with soil correction (liming and gypsum) and nitrogen (N) fertilization, but it is not clear how these factors might interact to affect humic substances. The objective of the study was to evaluate the effects of calcium (Ca), magnesium (Mg), and N fertilizatilizer amendments on the accumulation of C, N, and humic substances in soil aggregates from an Oxisoil in Brazil. The production system was no-till soybean [Gycine max (L.) Merr.] double-cropped with maize (Zea mays L.) and intercropped with forage grass since 2016. Treatments were no amendment, lime only, and lime + phosphogypsum, factorially arranged with and without annual N fertilization of maize. Soil was collected at 0–10, 10–20, 20–40, and 40–60 cm 6 years after initiation of the experiment. The combination of lime, gypsum, and N led to 13% greater total C stock and 20% greater total N stock within the 0–60 cm soil profile than the control. Levels of fulvic acid (FA) and humic acid (HA) were similar among aggregate classes, but humin was greatest in larger aggregates. Liming plus N decreased FA and HA, but gypsum application mitigated this negative effect. Application of limestone, gypsum, and N increased humin, mainly in the soil surface (0–10 cm). Soil C storage and stabilization was enhanced in large soil aggregates with the combined use of lime, gypsum, and N fertilization in humid tropical soils.